Voting on Independence and National Issues: A Historical and Comparative Study of Referendums on Self-Determination and Secession - Matt Qvortrup (Revue Française de Civilisation Britannique)
To date there have been fifty independence referendums. Some have been official, others unofficial. Some have been successful, and others have ended in failure. This article analyses how independence referendums have contributed to more civic engagement and how this use of the referendum can - under certain circumstances - enhance the ideals of participation espoused by the likes of Rousseau, Tocqueville and Mill.